Histological assessment of a novel restorative coronary artery bypass graft in a chronic ovine model - Sato, Yu; Kutnya, Matthew; Abebe, Biniyam; El Kurdi, Mohammed S.; Cox, Martijn; Bianco, Richard W.; Meuris, Bart; Onuma, Yoshinobu; Serruys, Patrick W.; Virmani, Renu (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundAlthough prosthetic conduits for coronary artery bypass grafting (CABG) are increasingly needed because of the limited availability and patency of autologous conduits, no alternatives have succeeded.MethodsSixteen sheep underwent CABG. Thirteen received a bioabsorbable polymer graft with an incorporated nitinol microskeleton (Xeltis coronary artery bypass graft [XABG]), and three received autologous saphenous vein grafts (SVG). Pathological evaluation was conducted at 12 months.ResultsIn the XABG group, two sheep died perioperatively; two were sacrificed at 3 months (1 occluded, 1 patent) and two at 6 months (both patent). Two more died from occlusion at 9–10 months, and five survived with patent grafts at 12 months. All SVGs remained patent for 12 months. Histology demonstrated near-complete luminal endothelialization in XABG, with increased polymer adsorption and matrix deposition. The cross-sectional area of the SVG lumen was significantly larger than XABGs (48.2 mm2 vs 12.9 mm2, p = 0.0018), consistent with a reduced angiographic flow velocity in SVG. The neointimal area was greater in SVGs than XABGs (19.6 vs. 6.7 mm2, p = 0.0005), especially at the distal ends of SVGs due to thrombus formation.ConclusionXABG demonstrated 1-year feasibility with consistent endothelialization and polymer absorption. While SVGs had better patency, they showed greater diametrical irregularity and subsequent neointimal proliferation.